(untitled) (Contemporary Mathematics, 2025)
This paper retrieves perturbed quiescent optical solitons for the Fokas-Lenells equation that is considered with generalized quadratic-cubic form of self-phase modulation and nonlinear chromatic dispersion. The model is taken up with linear temporal evolution as well as with generalized temporal evolution. Two integration approaches are implemented to make this retrieval possible. The enhanced Kudryashov’s approach and the projective Riccati equation scheme recovers a wide range of such solitons. The numerical scheme displays a few simulations to such solitons.